Child Language Brokering Among Migrant/Refugee Communities in Türkiye - Özge Bayraktar Özer (İstanbul Üniversitesi Çeviribilim Dergisi)
Children who most quickly assimilate the language and social and cultural norms of the host country in a family carry out interpreting tasks for their families in diﬀerent contexts shortly after migration. In this regard, child interpreters, also referred to as child language brokers, play a role in facilitating communication at the language level and in fostering interaction between migrant/refugee and host communities. Child language brokering (CLB), a phenomenon usually studied in the context of immigrant/refugee communities, can be deﬁned as a form of non-professional community interpreting. However, it has yet to be addressed as a research area within the ﬁeld of translation studies in Türkiye. Although it has been examined from the perspectives of educational science and developmental psychology for many years in international literature, child language brokering is fundamentally an interpreting activity that awaits the attention of translation studies. This study aims to bridge this gap by exploring the phenomenon of child language brokering, which has been addressed by various disciplines for years in countries with high levels of migration, in the context of migrant/refugee communities in Türkiye. To this end, semi-structured interviews were conducted with six participants aged 18-21 who migrated to Türkiye from diﬀerent countries and engaged in language brokering activities for their families during their childhood. The interview ﬁndings, analysed through thematic analysis, shed light on the brokering settings in Türkiye where child language brokering is most needed, the concept of primary language brokering, contributions of language brokering, child language brokers’ feelings regarding their activities, and the responsibilities they undertake.